Is it the End of the Ice Age? - Susan Y Kwiecien (International Journal of Sports Physical Therapy)
The use of the RICE (Rest, Ice, Compression, Elevation) protocol has been the preferred method of treatment for acute musculoskeletal injuries for decades. However, the efficacy of using ice as a recovery strategy following injury in humans remains uncertain, and there is a growing trend recommending against icing following injury. Animal models suggest that while ice can help to accelerate the recovery process, extreme muscle cooling might delay repair and increase muscle scarring. Despite the conflicting evidence, ice should not be dismissed as a potential treatment option. When considering what is known about the injury cascade, the optimal application window for ice is in the immediate acute stage following injury to reduce the proliferation of secondary tissue damage that occurs in the hours after the initial injury. Practitioners should tailor the application of ice based on the injury timeline and repair process, consistent with applications in 20-30 minute intervals within the first 12 hours post-injury. Until the evidence unanimously proves otherwise, the culture of icing injuries should remain a staple in sports medicine.